Different evolution in the treatment of a severe persistent asthma in 2 twins: Case report and review of the literature. Issue 49 (December 2017) - Ioniuc, Ileana; Miron, Ingrith; Ignat, Ancuta; Lupu, Vasile Valeriu; Gavrilovici, Cristina; Starcea, Magdalena; Mitrofan, Elena Cristina; Murgu, Alina
Abstract: Rationale: Asthma is a multifactorial disease with complex genetic inheritance. In children under the age of 5 years, the diagnosis of asthma is a challenge. Patient concern: We present the case of twin sisters under the same treatment for persistent asthma, but with different evolution over the time. Diagnoses: One of the sister is diagnosed with severe persistent bronchial asthma associated with bronchiectasis and dyslipidemia and the other one only with mild persistent asthma. Interventions: At each admission the treatment for the exacerbations and the underlying respiratory infections was represented by antibiotics, short-acting β2 agonists, and, sometimes, oxygen and systemic corticosteroids. As chronic treatment, they received in the last period inhaled corticosteroids associated with long-acting β2 agonist. Outcomes: Until the age of 6.5 years, they had similar diagnoses and treatment; from this point one was asymptomatic, with normal pulmonary function tests. The other one had a more complicated evolution which led to a severe crisis by the age of 10 years old. Lessons: Although asthma is a multifactorial disease with complex genetic inheritance, the genetics has its limits. Our twins had a similar onset with the same genetic inheritance, with the same risk factors, with the same comorbidities and with the same treatment. In this context, different evolutions of severe persistent asthma require more extensive genetic investigations. Patient concern: We present the case of twin sisters under the same treatment for persistent asthma, but with different evolution over the time.